Preparation method of C70 high-strength anticorrosive concrete containing composite mineral admixture
Patent Information
- Application Number
- CN202610642287.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-11
- Publication Date
- 2026-09-11
AI Technical Summary
[0003]然而,现有高强混凝土技术在实际工程应用中仍面临诸多亟待解决的现实难题
1.本发明通过“插层改性-碱激发协同”技术,使偏高岭土层间距有效扩展,暴露足量活性位点,与其他矿物掺合料协同生成三维互穿网络结构,将混凝土内部连通孔隙转化为封闭凝胶孔,大幅提升胶凝体系密实度与界面粘结强度。同时,低钙硅比C-S-H凝胶、水化铝酸钠与CaCO3微晶的定向交织,进一步强化结构支撑,使混凝土具备优异的抗压强度,能够满足超深井筒、重载结构等对材料承载能力的严苛要求。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete technology, and in particular to a method for preparing C70 high-strength anti-corrosion concrete containing composite mineral admixtures. Background Technology
[0002] As engineering construction expands into deeper and more complex environments, ultra-deep main shafts, marine engineering projects, and chemical structures place higher demands on concrete performance. C70 high-strength concrete, with its excellent load-bearing capacity, has become one of the core structural materials for these projects. To achieve high-strength concrete, existing technologies generally employ a composite cementitious system of "high-grade cement + mineral admixtures + high-efficiency water-reducing agents." Strength is enhanced by optimizing aggregate gradation and adjusting the water-cement ratio. The application of mineral admixtures (such as mineral powder, fly ash, and silica fume) not only replaces some cement but also improves the microstructure of concrete through the pozzolanic effect, making it a key technological path for high-strength concrete preparation. Simultaneously, to adapt to complex construction conditions such as ultra-deep pumping, the industry also optimizes concrete fluidity and workability by compounding polycarboxylate superplasticizers and adding slump-retaining components, promoting the large-scale application of high-strength concrete in engineering projects.
[0003] However, existing high-strength concrete technology still faces many practical challenges in its application in engineering projects. In special scenarios such as ultra-deep well shafts, concrete must meet the requirements for long-distance transportation. While existing solutions can improve initial fluidity, the slump loss is rapid, easily leading to increased pumping pressure and pipe blockage risk, thus affecting construction efficiency. In pursuit of high strength, some solutions rely excessively on high cement content or the layering of single mineral admixtures, which not only leads to concentrated heat of hydration and causes early plastic cracks but also results in insufficient durability of concrete in corrosive environments such as sulfates and chloride ions, shortening the service life of the project. In addition, most existing mineral admixtures are directly added, making it difficult to fully activate their active components. The layered structure or agglomeration characteristics of some minerals lead to uneven dispersion, failing to fully exert their filling and reinforcing effects, resulting in limited strength improvement and performance fluctuations. At the same time, the high cost and high carbon emissions caused by high cement content contradict the development concept of green building, necessitating a balance between economy and environmental protection while ensuring high performance.
[0004] In view of the current shortcomings of high-strength concrete in terms of fluidity stability, high strength crack resistance synergy, corrosion resistance and durability, and economy, how to develop a C70 grade concrete preparation method that combines excellent high strength performance, high fluidity, strong crack resistance and corrosion resistance, and controllable cost through technological innovations such as modification and activation of mineral admixtures and synergistic adaptation of components has become an urgent technical issue to be addressed in the industry, and is also the key to meeting the needs of complex engineering construction and long-term service. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a method for preparing C70 high-strength anti-corrosion concrete containing composite mineral admixtures.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing C70 high-strength anti-corrosion concrete containing composite mineral admixtures, comprising the following steps: (1) Place metakaolin in an oven to dry until the moisture content is ≤5%, cool to room temperature and then crush it through a 100-mesh sieve. Then add it to anhydrous ethanol with hexadecyltrimethylammonium bromide, heat to 50-70℃ and stir for 1-3 hours. Then separate the reaction product by centrifugation, remove the supernatant, wash the obtained solid product and place it in an oven to dry. After cooling, crush it through a 120-mesh sieve to obtain modified metakaolin. (2) Add S95 mineral powder, Class I fly ash, SF85 silica fume, modified metakaolin, and anhydrous sodium carbonate into a forced mixer and dry mix for 60-120s to obtain modified composite mineral admixture; (3) Prepare cement, modified composite mineral admixture, coarse aggregate, fine aggregate, admixture, crack-resistant and corrosion-resistant agent and water; (4) Mix the admixture and 40% water evenly to prepare an admixture solution; (5) Put coarse aggregate and fine aggregate into a mixer, add cement and modified composite mineral admixture, add the remaining 60% water, stir for 20-40s, then add 60% admixture aqueous solution, stir for 60-120s, then add the remaining 40% admixture aqueous solution and continue stirring for 30-90s. The total stirring time is not less than 180s to obtain a C70 high-strength anti-corrosion concrete containing composite mineral admixture.
[0007] Preferably, in (1), metakaolin, hexadecyltrimethylammonium bromide and anhydrous ethanol are in a weight ratio of 1:0.05-0.1:20-30.
[0008] Preferably, the temperature of the oven in (1) is 80-105℃.
[0009] Preferably, in (2), the weight ratio of S95 mineral powder, Class I fly ash, SF85 silica fume, modified metakaolin and anhydrous sodium carbonate is 8-10:4-6:4-6:1.2-1.8:0.2-0.4.
[0010] Preferably, the S95 mineral powder in (2) has an activity index ≥95% and a fluidity ratio ≥95%.
[0011] Preferably, the fineness of the Class I fly ash in (2) is ≤12%, the water requirement ratio is ≤94%, and the loss on ignition is ≤5%.
[0012] Preferably, the SF85 silica fume in (2) has a SiO2 content ≥85% and a specific surface area ≥15m². 2 / g.
[0013] Preferably, in step (3), cement, modified composite mineral admixture, coarse aggregate, fine aggregate, additives, crack-resistant and corrosion-resistant agent and water are prepared in a weight ratio of 40-42:20-21.6:90-92:80-86:10-14:0.5-0.66:140-150.
[0014] Preferably, the cement in (3) refers to P·O42.5 ordinary Portland cement.
[0015] Preferably, the coarse aggregate in (3) refers to high-strength basalt crushed stone with a crushing value ≤10%, needle-like and flaky content ≤8%, mud content ≤0.5%, water absorption rate ≤1.0%, and particle size 5-16mm.
[0016] Preferably, the fine aggregate in (3) refers to limestone manufactured sand with a fineness modulus of 2.9±0.1 and performance indicators that meet the following requirements: MB value ≤1.0, stone powder content 3-5%, and water absorption rate ≤1.8%.
[0017] Preferably, the additives in (3) refer to a mixture of polyether polycarboxylate superplasticizer, ester polycarboxylate superplasticizer, polyether slump retainer, sodium gluconate, mineral oil defoamer and rosin soap air-entraining agent in a weight ratio of 50-60:30-40:6-10:2-5:0.1-0.4.
[0018] Preferably, the crack-resistant and corrosion-resistant agent in (3) refers to K2LS crack-resistant and seepage-resistant composite agent.
[0019] Preferably, the mixer in (5) refers to a forced twin-shaft mixer or a planetary mixer, and the capacity of the mixer should meet the requirements of the single batch of concrete to avoid overloading or underloading.
[0020] Preferably, the mechanism of action of the method for preparing C70 high-strength anti-corrosion concrete containing composite mineral admixtures in this invention is explained as follows: This invention achieves a comprehensive improvement in the high strength, high fluidity, crack resistance, corrosion resistance, and economy of C70 concrete through an integrated design of "intercalation modification - alkali activation synergy - multi-component adaptation". Its core mechanism of action is as follows: First, the intercalation activation of modified metakaolin is fundamental to performance improvement. Metakaolin, as a highly reactive aluminosilicate mineral, naturally possesses a layered crystal structure, with layers connected by hydrogen bonds. This results in the active Al₂O₃ sites being encapsulated, hindering their full participation in the reaction. This invention uses hexadecyltrimethylammonium bromide (CTAB) as an intercalating agent. In an anhydrous ethanol dispersion system, CTAB dissociates to generate long-chain alkyl cations (C₂, C₃, C₄).16 H 33 N(CH3)3 + The cation replaces the exchangeable cations between metakaolin layers through ion exchange and binds to the surface of the layers by van der Waals forces, disrupting the interlayer hydrogen bond network and increasing the interlayer spacing of metakaolin. This process not only exposes a large number of encapsulated active Al2O3 reaction sites, but also provides "growth space" for the subsequent hydration product formation, avoiding product aggregation and laying the structural foundation for the full progress of the subsequent alkali-activated reaction. At the same time, the long-chain alkyl group of CTAB forms an adsorption layer on the surface of metakaolin, which can initially improve its compatibility with cement paste and enhance the dispersion uniformity.
[0021] Secondly, the synergistic "intercalation-alkali activation" reaction of the composite mineral admixture is the core to achieving high strength and density. Anhydrous sodium carbonate in the composite mineral admixture dissolves rapidly in the mixing water, undergoing a dissociation reaction: Na₂CO₃ → 2Na + +CO3 2- In the initial stage of cement hydration, a large amount of Ca(OH)2 is generated, creating a highly alkaline environment with a pH ≥ 12.5. At this time, CO32- 2- It reacts chemically with Ca(OH)2: Na2CO3 + Ca(OH)2 → CaCO3↓ + 2NaOH, generating CaCO3 microcrystals that can initially fill the pores in the interface transition zone between cementitious materials and aggregates, reducing early porosity; at the same time, the NaOH generated by the reaction further enhances the alkalinity of the system and activates the synergistic reaction of each component in the composite mineral admixture: the active Al2O3 exposed by modified metakaolin undergoes a hydration reaction with NaOH and H2O: 2Al2O3 + 2NaOH + 6H2O → 2Na2Al2O4·4H2O (sodium aluminate hydrate); the active SiO2 in silica fume, S95 mineral powder and Class I fly ash undergoes a pozzolanic reaction with Ca(OH)2 and H2O: SiO2 (active) + Ca(OH)2 + H2O → xCaO·SiO2·yH2O (low calcium-to-silicon ratio CSH gel, C / S = 1.0~1.2). Because the intercalation structure of modified metakaolin provides a template for directional growth, sodium aluminate hydrate and low calcium silicate ratio CSH gel are precipitated directionally along the interlayer channels and intertwine with CaCO3 microcrystals to form a three-dimensional interpenetrating network structure of "nanogel-microcrystal-lamellae". This transforms the interconnected capillary pores inside the concrete into closed gel pores, resulting in a decrease in porosity compared to traditional C70 concrete. This significantly improves the density and interfacial bonding strength of the cementitious system, providing structural support for high-strength performance.
[0022] Furthermore, the synergistic effect of the admixture compound ensures the high fluidity and construction adaptability of concrete. This invention uses a compound of polyether and ester-based polycarboxylate superplasticizers. The carboxyl groups (-COOH) in the polycarboxylate superplasticizer molecular chain adsorb onto the surface of cement and mineral admixture particles, forming electrostatic repulsion. At the same time, the polyether side chains extend to form a steric hindrance effect, breaking down particle agglomerates and releasing the encapsulated free water, thereby improving the slump and spread of concrete. The compounded polyether slump retainer releases slump-retaining components through slow hydrolysis, and works synergistically with sodium gluconate retarder to extend the cement hydration induction period. This avoids the rapid loss of slump caused by the concentrated heat of hydration in the early stage of the alkali-activated reaction, and provides sufficient time for the "intercalation-alkali activation" reaction to ensure the full generation of nano-products. The mineral oil defoamer can eliminate large air bubbles generated during the mixing process, and the rosin soap air-entraining agent introduces uniformly distributed micro-bubbles (with an air content of 3%-5%), further optimizing the internal structure of concrete and balancing fluidity and density.
[0023] Finally, the crack resistance and corrosion protection stem from the combined effect of the dense structure and functional components. On the one hand, the three-dimensional interpenetrating network structure generated by "intercalation-alkali activation" significantly reduces the porosity and pore connectivity of concrete, forming a physical barrier that blocks the penetration paths of corrosive media such as sulfates and chloride ions. At the same time, CaCO3 microcrystals and CSH gel synergistically fill the microcracks in the interface transition zone, improving the overall structural integrity and reducing the channels for corrosive media intrusion. On the other hand, the active components in the K2LS crack-resistant and impermeable composite agent react chemically with cement hydration products to generate insoluble calcium salt complexes, which cover the surface of cementitious material particles and the inner walls of pores, forming a hydrophobic film that reduces the adsorption capacity of media and greatly increases the resistance to sulfate erosion. Meanwhile, the hydration reaction rate of the composite mineral admixture is slow, and combined with the dispersion effect of the three-dimensional network on shrinkage stress, it effectively reduces plastic shrinkage cracks and drying shrinkage cracks, significantly improving the long-term durability of concrete.
[0024] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention utilizes an "intercalation modification-alkali activation synergy" technology to effectively expand the interlayer spacing of metakaolin, exposing sufficient active sites. This, in conjunction with other mineral admixtures, generates a three-dimensional interpenetrating network structure, transforming the interconnected pores within the concrete into closed gel pores, significantly improving the density and interfacial bond strength of the cementitious system. Simultaneously, the directional interweaving of low-calcium-silica ratio CSH gel, hydrated sodium aluminate, and CaCO3 microcrystals further strengthens the structural support, giving the concrete excellent compressive strength, capable of meeting the stringent requirements for material load-bearing capacity in ultra-deep well shafts and heavy-duty structures.
[0025] 2. The composite mineral admixture used in this invention undergoes thorough intercalation modification and uniform dispersion. Combined with the electrostatic repulsion and steric hindrance effects of the compounded admixtures, it effectively reduces the yield stress of the concrete mixture, releases trapped free water, and significantly improves slump and spread. The synergistic effect of the high slump-retaining components and the retarder suppresses slump loss, ensuring the stability of the concrete during long-distance transportation and ultra-deep pumping, reducing frictional resistance and the risk of pipe blockage in the delivery pipe, and meeting the high-efficiency operation requirements of complex construction environments.
[0026] 3. The dense three-dimensional interpenetrating network in this invention can effectively disperse the shrinkage stress during the setting and hardening process of concrete, avoiding the initiation of cracks caused by stress concentration; the hydrophobic film generated by the reaction of K2LS crack-resistant and corrosion-resistant agent with cement hydration products further blocks the penetration paths of corrosive media such as sulfates and chloride ions. Under the dual protection, the early plastic crack rate of concrete is significantly reduced, and the resistance to sulfate attack and chloride ion penetration is significantly improved, extending the service life in complex corrosive environments and reducing later maintenance costs.
[0027] 4. This invention optimizes the proportions of cementitious materials, rationally controlling the amount of cement while ensuring high performance, and fully utilizing industrial by-products such as mineral powder and fly ash as mineral admixtures. This reduces the unit cost of concrete and achieves resource utilization of industrial solid waste. Simultaneously, the optimized cement usage reduces carbon emissions during production, and the anhydrous ethanol in the modification process can be recycled and reused, aligning with the concepts of green building and low-carbon development, thus balancing economic and environmental benefits. Detailed Implementation
[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0029] Example 1: A specific preparation method of C70 high-strength anti-corrosion concrete containing composite mineral admixtures, comprising the following steps: (1) Place 100g of metakaolin in an oven at 80℃ and dry it until the water content is ≤5%. After cooling to room temperature, crush it through a 100-mesh sieve. Then add it and 5g of hexadecyltrimethylammonium bromide to 2kg of anhydrous ethanol. Heat to 50℃ and stir for 1h. Then separate the reaction product by centrifugation, remove the supernatant, wash the obtained solid product, dry it in an oven at 85℃, cool it and crush it through a 120-mesh sieve to obtain modified metakaolin. (2) Take 80g of S95 mineral powder (activity index ≥95%, fluidity ratio ≥95%), 40g of Grade I fly ash (fineness ≤12%, water requirement ratio ≤94%, loss on ignition ≤5%), and 40g of SF85 silica fume (SiO2 content ≥85%, specific surface area ≥15m²). 212g of modified metakaolin and 2g of anhydrous sodium carbonate were added to a forced mixer and dry-mixed for 60s to obtain a modified composite mineral admixture. (3) Prepare 400g of cement (P·O42.5 ordinary Portland cement), 200g of modified composite mineral admixture, 900g of coarse aggregate (high-strength basalt crushed stone, crushing value ≤10%, needle-like and flaky content ≤8%, mud content ≤0.5%, water absorption rate ≤1.0%, particle size 5-16mm), 800g of fine aggregate (limestone manufactured sand, fineness modulus 2.9±0.1, performance indicators meet: MB value ≤1.0, stone powder content 3-5%, water absorption rate ≤1.8%), 100g of admixture (polyether polycarboxylate superplasticizer, ester polycarboxylate superplasticizer, polyether slump retainer, sodium gluconate, mineral oil defoamer and rosin soap air-entraining agent mixed in a weight ratio of 50:30:6:2:0.1), 5g of K2LS crack-resistant and impermeable composite agent and 1.4kg of water; (4) Mix the admixture and 560g of water evenly to prepare an admixture solution; (5) Put coarse aggregate and fine aggregate into a mixer, add cement and modified composite mineral admixture, add the remaining 60% of 840g water, stir for 20s, then add 60% of the admixture aqueous solution, stir for 120s, then add the remaining 40% of the admixture aqueous solution and continue stirring for 40s to obtain a C70 high-strength anti-corrosion concrete containing composite mineral admixture.
[0030] Example 2: A specific preparation method for C70 high-strength anti-corrosion concrete containing composite mineral admixtures, comprising the following steps: (1) Place 100g of metakaolin in an oven at 90℃ and dry it until the water content is ≤5%. After cooling to room temperature, crush it through a 100-mesh sieve. Then add it and 8g of hexadecyltrimethylammonium bromide to 2.5kg of anhydrous ethanol. Heat to 60℃ and stir for 2h. Then separate the reaction product by centrifugation, remove the supernatant, wash the obtained solid product, dry it in an oven at 90℃, cool it and crush it through a 120-mesh sieve to obtain modified metakaolin. (2) Take 90g of S95 mineral powder (activity index ≥95%, fluidity ratio ≥95%), 50g of Grade I fly ash (fineness ≤12%, water requirement ratio ≤94%, loss on ignition ≤5%), and 50g of SF85 silica fume (SiO2 content ≥85%, specific surface area ≥15m²). 2 15g of modified metakaolin and 3g of anhydrous sodium carbonate were added to a forced mixer and dry-mixed for 90s to obtain a modified composite mineral admixture. (3) Prepare 410g of cement (P·O42.5 ordinary Portland cement), 208g of modified composite mineral admixture, 910g of coarse aggregate (high-strength basalt crushed stone, crushing value ≤10%, needle-like and flaky content ≤8%, mud content ≤0.5%, water absorption rate ≤1.0%, particle size 5-16mm), 830g of fine aggregate (limestone manufactured sand, fineness modulus 2.9±0.1, performance indicators meet: MB value ≤1.0, stone powder content 3-5%, water absorption rate ≤1.8%), 120g of admixture (polyether polycarboxylate superplasticizer, ester polycarboxylate superplasticizer, polyether slump retainer, sodium gluconate, mineral oil defoamer and rosin soap air-entraining agent mixed in a weight ratio of 55:35:8:3:0.3), 5.8g of K2LS crack-resistant and impermeable composite agent and 1.45kg of water; (4) Mix the admixture and 580g of water evenly to prepare an admixture solution; (5) Put coarse aggregate and fine aggregate into a mixer, add cement and modified composite mineral admixture, add 870g of water, stir for 30s, then add 60% of admixture aqueous solution, stir for 90s, then add the remaining 40% of admixture aqueous solution and continue stirring for 60s to obtain a C70 high-strength anti-corrosion concrete containing composite mineral admixture.
[0031] Example 3: A specific preparation method for C70 high-strength anti-corrosion concrete containing composite mineral admixtures, comprising the following steps: (1) Place 100g of metakaolin in an oven at 105℃ and dry it until the moisture content is ≤5%. After cooling to room temperature, crush it through a 100-mesh sieve. Then add it and 10g of hexadecyltrimethylammonium bromide to 3kg of anhydrous ethanol. Heat the mixture to 70℃ and stir for 3h. Then separate the reaction product by centrifugation, remove the supernatant, wash the obtained solid product, dry it in an oven at 105℃, cool it, crush it through a 120-mesh sieve, and obtain modified metakaolin. (2) Combine 100g of S95 mineral powder (activity index ≥95%, fluidity ratio ≥95%), 60g of Grade I fly ash (fineness ≤12%, water requirement ratio ≤94%, loss on ignition ≤5%), and 60g of SF85 silica fume (SiO2 content ≥85%, specific surface area ≥15m²). 2 18g of modified metakaolin and 4g of anhydrous sodium carbonate were added to a forced mixer and dry-mixed for 120s to obtain a modified composite mineral admixture. (3) Prepare 420g of cement (P·O42.5 ordinary Portland cement), 216g of modified composite mineral admixture, 920g of coarse aggregate (high-strength basalt crushed stone, crushing value ≤10%, needle-like and flaky content ≤8%, mud content ≤0.5%, water absorption rate ≤1.0%, particle size 5-16mm), 860g of fine aggregate (limestone manufactured sand, fineness modulus 2.9±0.1, performance indicators meet: MB value ≤1.0, stone powder content 3-5%, water absorption rate ≤1.8%), 140g of admixture (polyether polycarboxylate superplasticizer, ester polycarboxylate superplasticizer, polyether slump retainer, sodium gluconate, mineral oil defoamer and rosin soap air-entraining agent mixed in a weight ratio of 60:40:10:5:0.4), 6.6g of K2LS crack-resistant and impermeable composite agent and 1.5kg of water; (4) Mix the admixture and 600g of water evenly to prepare an admixture solution; (5) Put coarse aggregate and fine aggregate into a mixer, add cement and modified composite mineral admixture, add 900g water, stir for 40s, then add 60% admixture aqueous solution, stir for 120s, then add the remaining 40% admixture aqueous solution and continue stirring for 90s to obtain a C70 high-strength anti-corrosion concrete containing composite mineral admixture.
[0032] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is omitted and metakaolin is not modified by hexadecyltrimethylammonium bromide.
[0033] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is omitted and modified metakaolin is not added in step (2).
[0034] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that anhydrous sodium carbonate is not added in step (2).
[0035] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (1) is omitted and modified metakaolin and anhydrous calcium carbonate are not added in step (2).
[0036] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that K2LS anti-crack and anti-permeability composite agent is not added.
[0037] Performance testing: 1. Slump and Spread Tests: Tests were conducted according to the "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" (GB / T50080-2016). Concrete mixtures prepared in each example and comparative example were loaded into a slump cone (100mm upper diameter, 200mm lower diameter, 300mm height) in three layers. Each layer was compacted vertically and evenly 25 times with a φ16mm tamping rod. After leveling off excess mixture at the cone opening, the slump cone was lifted steadily and vertically (lifting time controlled within 5-10 seconds). The maximum distance the mixture slumped naturally was measured, which was the slump value. Subsequently, a steel ruler was used to measure the two mutually perpendicular diameters of the circular spread surface formed by the slumped mixture on the horizontal plane, and the average value was taken as the spread value. The experimental results are shown in Table 1.
[0038] 2.28-day compressive strength test: The test was conducted in accordance with the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T 50081-2019). The concrete mixtures prepared for each experiment and the comparative example were placed into standard 150mm×150mm×150mm cube molds, compacted in three layers using vibration, leveled, and then cured in a standard curing room at 20±2℃ and ≥95% humidity for 28 days. After curing, the molds were removed and demolded, and the compressive strength was tested using a hydraulic pressure testing machine. The loading rate was controlled at 0.5-0.8MPa / s until the specimen failed. The maximum failure load was recorded, and the compressive strength was calculated using the formula: failure load / specimen compression area. The experimental results are shown in Table 1.
[0039] 3. Pumping Pressure Test: Simulating the construction conditions of an ultra-deep main shaft (≥750m), a concrete pumping test device was used for testing. The test device consisted of a mixing and storage silo, a high-pressure delivery pump, a simulated shaft delivery pipe (125mm diameter, wall thickness ≥4.5mm, total length equivalent to a delivery height of 750m), and pressure sensors. The concrete mixtures prepared for each experiment and comparative example were poured into the storage silo, the pumping equipment was started, and the delivery speed was controlled at 0.8-1.0m / s. 3 / h, after the pumping stabilizes, the stable pressure value at the outlet of the delivery pipe is read by the pressure sensor, which is the pumping pressure. The experimental results are shown in Table 1.
[0040] 4. Early Plastic Crack Rate Test: The plate method was conducted according to the appendix of the "Code for Acceptance of Construction Quality of Concrete Structures" (GB 50204-2015). Concrete samples prepared in the examples and comparative examples were made into 800mm×600mm×100mm plate specimens and placed in an environmental chamber with a temperature of 25±2℃, relative humidity of 60±5%, and wind speed of 0.5-1.0m / s. A crack width observation instrument was used for continuous observation for 72 hours, recording the length and width of all plastic cracks appearing on the specimen surface. The crack area ratio was calculated using the formula: Crack area ratio = Sum of all crack areas / Total surface area of the specimen × 100%. The experimental results are shown in Table 1.
[0041] 5.28-day sulfate attack resistance test: The rapid immersion method was performed according to the "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2024). Concrete samples prepared in the examples and comparative examples were made into 100mm×100mm×100mm cube specimens. After 28 days of standard curing, the specimens were immersed in a 5% (mass fraction) sodium sulfate solution at a temperature of 20±2℃, with the solution changed every 7 days. After 28 days of immersion, the specimens were removed, and their compressive strength was measured. The sulfate attack resistance rate was calculated using the formula: (Compressive strength of the immersed group / Initial compressive strength) × 100%. The experimental results are shown in Table 1.
[0042] 6.28-day chloride ion penetration resistance coefficient test: The Rapid Chloride Ion Migration Method (RCM method) was used for testing according to GB / T50082-2009. Concrete samples prepared in the examples and comparative examples were made into cylindrical specimens with a diameter of φ100mm × 50mm. After standard curing for 28 days, the two ends of the specimens were placed in a cathode cell containing 3% NaCl solution and an anode cell containing 0.3mol / L NaOH solution, respectively. A DC voltage of 60V was applied, and the test temperature was maintained at 20±2℃ for 24 hours. After the test, the specimens were cut along the axial direction, and 0.1mol / L silver nitrate solution was sprayed on the cut surface. The chloride ion penetration depth was measured, and the 28-day chloride ion penetration resistance coefficient was calculated according to the RCM method formula. The experimental results are shown in Table 1.
[0043] Table 1 Performance Test Results
[0044] Data Analysis: As can be seen from the performance test data in Table 1, the embodiments of the present invention, through the integrated technical design of "intercalation modification-alkali activation synergy-multi-component adaptation", show significant advantages in terms of fluidity, strength, crack resistance, corrosion resistance and construction adaptability. The overall performance far exceeds that of the comparative examples, with Example 2 showing the best comprehensive performance.
[0045] Example 2 exhibits excellent flowability, likely due to the thorough intercalation activation of the modified metakaolin and the synergistic dispersion effect of the multiple components. CTAB reacts with metakaolin at suitable temperature and time, disrupting interlayer hydrogen bonds to expand the interlayer spacing to the ideal range and exposing sufficient active sites. Furthermore, the formation of an adsorption layer through long-chain alkyl groups improves compatibility with cement paste. Combined with the composite mineral admixture and thorough stirring, this ensures uniform dispersion of all components. The synergistic effect of polyether and ester-based polycarboxylate superplasticizers in the compounded admixtures disrupts particle agglomeration through electrostatic repulsion and steric hindrance, releasing encapsulated free water and further enhancing flowability. The fluidity of each comparative example was lower than that of Example 2 due to the lack of core technical features: Comparative Example 1 did not undergo intercalation modification of metakaolin, the interlayer spacing was not effectively expanded, the particle compatibility was poor and the active sites were not exposed enough, resulting in poor dispersion; Comparative Example 2 lacked metakaolin as a core active component, the "intercalation-alkali activation" synergistic reaction could not be initiated, and it was difficult to optimize the fluidity of the slurry by relying solely on the physical filling of a single mineral admixture; Comparative Example 3 lacked anhydrous sodium carbonate to provide an alkali activation environment, the alkalinity of the system was insufficient, and it was impossible to generate CaCO3 microcrystals to optimize the particle size distribution, thus suppressing the dispersibility; Comparative Example 4 lacked both modified metakaolin and anhydrous sodium carbonate, the core synergistic system was completely ineffective, and the fluidity was the worst; Comparative Example 5 only lacked K2LS crack-resistant and corrosion-preserving agent, which had a small impact on fluidity, but because there was no hydrophobic film to assist in optimizing the slurry state, the fluidity was slightly inferior to that of Example 2.
[0046] The high strength of Example 2 is attributed to the dense three-dimensional interpenetrating network structure formed by the synergistic effect of "intercalation-alkali activation". The appropriate amount of CTAB avoids the increase in gas content caused by excessive residue. The active Al2O3 exposed by the modified metakaolin reacts fully with the NaOH generated by the activation of anhydrous sodium carbonate to generate sodium aluminate hydrate. At the same time, the active SiO2 in silica fume, mineral powder, etc. reacts with Ca(OH)2 to generate low calcium-to-silicon ratio CSH gel. Both grow directionally along the intercalation channel and interweave with CaCO3 microcrystals to form a dense network, which significantly reduces porosity and strengthens the interfacial bonding strength. In comparison, the unmodified metakaolin in Comparative Example 1 resulted in the aggregation of nanoproducts, a loose three-dimensional network, and insufficient density; Comparative Example 2, lacking metakaolin to provide active Al2O3, could not form a complete three-dimensional network, and the strength could not be improved by relying solely on the volcanic ash effect; Comparative Example 3, due to the lack of an alkali activator, had insufficient activation of active components, resulting in a small amount of hydration products and poor network density; Comparative Example 4 lacked a core synergistic system and was merely a simple mixture of traditional cementitious materials, resulting in the lowest strength; Comparative Example 5, although retaining the three-dimensional network structure, lacked the calcium salt complexes generated by K2LS to fill the fine pores, resulting in slightly weaker interfacial bonding strength and slightly lower overall strength.
[0047] Example 2 has a lower pumping pressure, making it suitable for ultra-deep wellbore transportation needs. This is essentially due to the synergistic effect of excellent fluidity and slurry stability. Sufficient intercalation modification and uniform dispersion reduce the yield stress of the concrete mixture, while the high slump retention of the compound admixtures suppresses slump loss, ensuring slurry stability during transportation and reducing frictional resistance on the inner wall of the delivery pipe. The pumping pressures of all comparative examples are higher than those of Example 2: Comparative Example 1 suffers from insufficient fluidity and uneven slurry dispersion, leading to increased frictional resistance; the low fluidity of Comparative Examples 2 and 4 directly causes a surge in pumping resistance; Comparative Example 3 exhibits poor slurry stability, with particle aggregation easily occurring in some areas, increasing pumping pressure; although Comparative Example 5 has fluidity close to that of Example 2, the lack of a hydrophobic film protection in the slurry makes it easier for moisture to adhere to the pipe wall during transportation, resulting in slightly higher frictional resistance.
[0048] The low crack rate in Example 2 stems from the synergistic crack-resistant effect of the three-dimensional interpenetrating network and the K2LS crack-resistant agent. The dense three-dimensional network effectively disperses the plastic shrinkage stress and drying shrinkage stress during the concrete setting and hardening process, preventing crack initiation caused by stress concentration. The calcium salt complex generated by the reaction of K2LS with cement hydration products covers the inner wall of the pores, forming a hydrophobic film, reducing the rate of water evaporation, and further inhibiting crack development. The crack rates of each comparative example were higher than those of Example 2: the unmodified metakaolin in Comparative Example 1 resulted in a loose network structure and weak stress dispersion ability; Comparative Example 2 lacked metakaolin and had no complete network structure to support it, so stress could not be effectively transferred; Comparative Example 3 had insufficient alkali activation, resulting in poor network density and limited crack resistance; Comparative Example 4 lacked the core synergistic system and relied solely on the inherent properties of traditional materials, resulting in the highest crack rate; Comparative Example 5 lacked the K2LS crack-resistant agent, and without the hydrophobic film to assist in inhibiting water evaporation and crack propagation, the crack resistance effect was significantly reduced.
[0049] Example 2's superior resistance to sulfate attack is due to the dual protective barrier formed by its dense structure and hydrophobic film. The three-dimensional interpenetrating network seals most of the interconnected capillary pores, significantly reducing the penetration path of sulfate media; the hydrophobic film formed by the insoluble calcium salt complex generated by K2LS reduces the adsorption capacity of the media on the pore surface, further blocking the erosion path. The sulfate attack resistance of each comparative example is weaker than that of Example 2: Comparative Example 1's loose network structure results in high pore connectivity, allowing easy media penetration; Comparative Example 2 lacks a complete three-dimensional network, resulting in a missing protective barrier; Comparative Example 3 suffers from insufficient alkali activation, leading to poor network density and easy intrusion of corrosive media; Comparative Example 4 exhibits the most severe corrosion due to the failure of its core protective system and free media penetration; Comparative Example 5 lacks K2LS and has no hydrophobic film for auxiliary protection, resulting in enhanced media adsorption and penetration capacity and a decreased resistance rate.
[0050] The low chloride ion permeability coefficient of Example 2 is likely due to the synergistic barrier effect of the ultra-high density formed by "intercalation-alkali activation" and the hydrophobic membrane. The three-dimensional network formed by the directional growth of nano-hydration products and CaCO3 microcrystals transforms capillary pores into closed gel pores, significantly extending the chloride ion permeation path; the hydrophobic membrane generated by K2LS reduces the adsorption and diffusion rate of chloride ions on the pore surface, resulting in a significant reduction in chloride ion permeability under the dual effect. The permeability coefficients of each comparative example are higher than those of Example 2: the unmodified metakaolin in Comparative Example 1 leads to network aggregation and high pore connectivity, resulting in a short chloride ion permeation path; Comparative Example 2 lacks core active components and has no complete dense structure, resulting in low permeation resistance; Comparative Example 3 has insufficient alkali activation, resulting in low hydration product generation, high porosity, and a relatively large permeability coefficient; Comparative Example 4 lacks a core synergistic system, resulting in a loose pore structure inside the concrete, allowing for rapid chloride ion permeation; Comparative Example 5 lacks the hydrophobic membrane formed by K2LS, resulting in enhanced chloride ion adsorption and diffusion capacity and a significantly increased permeability coefficient.
[0051] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for producing a C70 high-strength anticorrosive concrete containing a composite mineral admixture, characterized by, It comprises the following steps: (1) Put the metakaolin into an oven to dry to a water content of ≤5%, crush it through a 100-mesh sieve after cooling to room temperature, then add cetyltrimethylammonium bromide into anhydrous ethanol, stir at a temperature of 50-70℃ for 1-3h, then centrifuge the reaction product, remove the supernatant, wash the obtained solid product, dry it in an oven, crush it through a 120-mesh sieve after cooling, and obtain the modified metakaolin; (2) Put S95 mineral powder, I-grade fly ash, SF85 silica ash, modified metakaolin, and anhydrous sodium carbonate into a forced mixer, dry mix for 60-120s, and obtain the modified composite mineral admixture; (3) Prepare cement, modified composite mineral admixture, coarse aggregate, fine aggregate, additive, anti-cracking and corrosion inhibitor, and water; (4) Mix the additive and 40% water to prepare an additive solution; (5) Put the coarse aggregate and fine aggregate into a mixer, add cement and modified composite mineral admixture, add the remaining 60% water, stir for 20-40s, then add 60% of the additive aqueous solution, stir for 60-120s, add the remaining 40% additive aqueous solution, and continue to stir for 30-90s, with a total stirring time of not less than 180s, to obtain a C70 high-strength corrosion-resistant concrete containing a composite mineral admixture.
2. The method of producing C70 high-strength anticorrosive concrete containing composite mineral admixtures according to claim 1, characterized in that, In the (1), the metakaolin, cetyltrimethylammonium bromide, and anhydrous ethanol are in a weight ratio of 1:0.05-0.1:20-30; and the temperature of the oven is 80-105℃.
3. The method of producing C70 high-strength anticorrosive concrete containing composite mineral admixtures according to claim 1, characterized in that, In the (2), the S95 mineral powder, I-grade fly ash, SF85 silica ash, modified metakaolin, and anhydrorous sodium carbonate are in a weight ratio of 8-10:4-6:4-6:1.2-1.8 :0.2-0.
4.
4. The method of producing C70 high-strength anticorrosive concrete containing composite mineral admixtures according to claim 1, characterized in that, The activity index of the S95 mineral powder in the (2) is ≥95%, and the fluidity ratio is ≥95%; the fineness of the I-grade fly ash is ≤12%, the water demand ratio is ≤94%, and the loss on ignition is ≤5%; the SiO2 content of the SF85 silica ash is ≥85%, and the specific surface area is ≥15 m 2 / g.
5. The method of producing C70 high-strength anticorrosive concrete containing composite mineral admixtures according to claim 1, characterized in that, In the (3), the cement, modified composite mineral admixture, coarse aggregate, fine aggregate, additive, anti-cracking corrosion inhibitor, and water are prepared in a weight ratio of 40-42:20-21.6:90-92:80-86:10 -14:0.5-0.66:140-150.
6. The method of producing C70 high-strength anticorrosive concrete containing composite mineral admixtures according to claim 1, characterized in that, In the (3), the cement refers to P·O42.5 ordinary portland cement.
7. The method of producing C70 high-strength anticorrosive concrete containing composite mineral admixtures according to claim 1, characterized in that, In the (3), the coarse aggregate refers to high-strength basalt macadam with a crushing value of ≤10%, a needle flake content of ≤8%, a clay content of ≤0.5%, a water absorption of ≤1.0%, and a particle size of 5-16mm; and the fine aggregate refers to limestone machine-made sand with a fineness modulus of 2.9±0.1 and performance indicators meeting the requirements of MB value ≤1.0 and stone powder content of 3-5% and water absorption of ≤1.8%.
8. The method of producing C70 high-strength anticorrosive concrete containing composite mineral admixtures according to claim 1, characterized in that, In the (3), the additive refers to a mixture of polyether polycarboxylic acid water reducer, ester polycarboxylic acid water reducer, polyether slump retaining agent, sodium gluconate, mineral oil defoamer, and rosin soap air entraining agent in a weight ratio of 50-60:30-40:6-10:2-5:0.1 -0.
4.
9. The method of producing C70 high-strength anticorrosive concrete containing composite mineral admixtures according to claim 1, characterized in that, In the (3), the anti-cracking corrosion inhibitor refers to K2LS anti-cracking and anti-permeability composite agent.
10. The method of producing C70 high-strength anticorrosive concrete containing composite mineral admixtures according to claim 1, characterized in that, In the (5), the mixer refers to a forced double-horizontal-shaft mixer or a planetary mixer, and the capacity of the mixer should meet the requirements of single-disk concrete quantity to avoid overloading or underloading.